The Attraction of Beach Tourism in Lampung and Its Influence on Tourist Interest - Pratama, Reza Hardian; Selvina, Mia; Alfredo, Harold Kevin; Darajat, Ulfah Alfiyah; Nursari, Ayu (JELAJAH: Journal of Tourism and Hospitality, 2025)
Tourism plays an important role in regional economic development, and beach tourism is one of the main attractions in Lampung. This study aims to analyze the attractiveness of beach tourism in Lampung and its influence on tourists' interest. Various factors such as natural beauty, accessibility, facilities, environmental sustainability, and promotional efforts are examined to determine their impact on tourists' interest in visiting. This study uses a Likert scale by distributing questionnaires through a purposive sampling method to 200 respondents, with Smart PLS 3.0 as the analytical tool. The results indicate that natural beauty, well-maintained infrastructure, and effective marketing strategies significantly influence tourists' interest. However, several challenges such as waste management, security issues, and limited public transportation remain obstacles in the development of beach tourism in this region. Findings from this study suggest that improving beach management, strengthening promotional strategies, and implementing sustainable tourism practices can further enhance tourists' interest in Lampung's beach destinations. This research provides valuable insights for local governments, tourism stakeholders, and business operators in developing more competitive and attractive beach tourism.